Generalized Dual Fibonacci Quaternions - Yuce, Salim; Aydin, Fugen Torunbalci (TSING HUA UNIV, DEPT MATHEMATICS, 2016)
In this paper, we defined the generalized dual Fibonacci quaternions. Also, we investigated the relations between different generalized dual Fibonacci quaternions. Furthermore, we gave the Binet's formulas and Cassini identities for these quaternions.
Keywords: Mathematics